Pathogenicity of Virulent Species of Group C Streptococci in Human - Marta Kłos; Jadwiga Wójkowska-Mach (Canadian Journal of Infectious Diseases and Medical Microbiology)
Group C streptococci (GCS) are livestock pathogens and they often cause zoonotic diseases in humans. They are Gram-positive, in mostly β-hemolytic and facultative anaerobes. Because of their close evolutionary kinship with group A streptococci (GAS), GCS share many common virulence factors with GAS and cause a similar range of diseases. Due to the exchange of genetic material with GAS, GCS belong to bacteria that are difficult to be distinguished from group A streptococci; GCS are often treated in microbiological diagnostics as contamination of the culture. This report focuses mainly on the pathogenicity of virulent species of GCS and their association with human diseases. The condition that is most frequently quoted is pharyngitis. In this paper, the virulence factors have also been mentioned and an interesting link has been made between GCS and the pathogenesis of rheumatic diseases among the native people of India and Aboriginal populations.